Which firms use targeted wage subsidies? An empirical note for Germany - Lutz Bellmann; Gesine Stephan (Journal for Labour Market Research, 2014)
In Germany, temporary wage subsidies (Eingliederungszuschüsse) can be granted to employers if they hire workers with obstacles to placement. Based on the 2003, 2005, 2007 and 2009 waves of the IAB Establishment Panel, this paper looks into the following questions: Is there a connection between the use of targeted wage subsidies and certain structural characteristics of the establishment, such as establishment size, industry and employment structure? Is the labor turnover of establishments that make use of wage subsidies higher than that of similar establishments that do not? Do establishments that utilize targeted wage subsidies also make use of other active labor market programs (e.g. work opportunities) to a disproportionate degree? On the whole, the empirical findings confirm that establishment structures are important for the decisions of firms to make use of targeted wage subsidies.
Keywords: 330; Eingliederungszuschuss - Inanspruchnahme; Betriebsgröße; Beschäftigtenstruktur; sektorale Verteilung; Wirtschaftszweige; IAB-Betriebspanel; labour turnover; arbeitsmarktpolitische Maßnahme; regionaler Vergleich; Qualifikationsstruktur; Tarifbindung; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland